A critical edition of the Historia Francorum Qui Ceperunt Iherusalem of Raymond of Aguilers - France, John (1967)
The Historia Francorum oui ceperunt Iherusalem is an eyewitness account of the First Crusade, written by a Provencal priest, Raymond of Aguilers, who accompanied the Count of Toulouse on the Crusade. As such it is an important primary source for the History of the First Crusade. Only ten manuscripts of the work of Raymond of Aguilers have survived, and the main purpose of this thesis has been, by collating these manuscripts, to restore the original text as written by Raymond of Aguilers. The evidence and reasoning which have led the present editor to construct the text herein contained, are to be found in the Critical Introduction. The work of Raymond of Aguilers has twice been previously edited: by Jaques Bongars in his collection of Crusader sources, the Gesta Dei per Francos (Hanover 1611); by various editors of the Academie Royale des Inscriptions et des Belles Lettres in their collection of Crusader sources, the Recueil des Historiens des Croisades; Historiens Occidentaux, (Paris, 1856). These editions are both, however, unsatisfactory, and the present text is the first to be constructed using all the known manuscripts of the work of Raymond of Aguilers. The Historia Francorum has always raised considerable difficulties of interpretation when it has been used as a source for the First Crusade. Recent work has tended to reduce these difficulties. In the Historical Introduction the editor has tried to give an account of the latest research, and to offer his suggestions as to how the Historia Francorum may best be used. The Historical Introduction has another purpose; in preparing the text it has been found necessary to take some account of the purposes and outloot of Raymond of Aguilers. Various matters of special interest, such as Raymond of Aguilers use of other eyewitness accounts of the First Crusade, have been dealt with in the Appendices.